2018
DOI: 10.3892/etm.2018.6586
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor 1 antagonism attenuates lipopolysaccharide‑induced activation of hepatic stellate cells via suppressing inflammation

Abstract: Activated hepatic stellate cells (HSCs) serve key roles in hepatic fibrosis by producing excessive extracellular matrix (ECM) components. Lipopolysaccharide (LPS) has been found to be associated with hepatic fibrogenesis through direct interactions with HSCs. Recently, the fibroblast growth factor receptor 1 (FGFR1) signalling system was identified as a key player in the process of liver fibrosis. In the present study it was evaluated whether FGFR1 mediated LPS-induced HSCs activation. In cultured cells, FGFR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In addition, evidence showed that FGF19 activated both FGFR1 and FGFR4 to a comparable extent in the presence of b-Klotho (Lan et al, 2017;Yang et al, 2012). FGFR1 inhibitor or genetic silencing by small interfering RNA significantly decreased the expression of a-SMA and type 1 collagen and reduced cell viability (Lou et al, 2018) and administration of FGF receptor inhibitor (PD173074) attenuated the activation of fibroblasts (MacKenzie et al, 2015). Those studies demonstrated that FGF19 could increase a-SMA, activate fibroblasts, and lead to the activation of CAFs.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, evidence showed that FGF19 activated both FGFR1 and FGFR4 to a comparable extent in the presence of b-Klotho (Lan et al, 2017;Yang et al, 2012). FGFR1 inhibitor or genetic silencing by small interfering RNA significantly decreased the expression of a-SMA and type 1 collagen and reduced cell viability (Lou et al, 2018) and administration of FGF receptor inhibitor (PD173074) attenuated the activation of fibroblasts (MacKenzie et al, 2015). Those studies demonstrated that FGF19 could increase a-SMA, activate fibroblasts, and lead to the activation of CAFs.…”
Section: Discussionmentioning
confidence: 91%
“…EGFR inhibitor erlotinib inhibited proliferation of the cholangiocytes and hepatocytes, and prevented activation of HSCs, which was demonstrated on different (CCl 4 -, diethylnitrosamine (DEN)-and BDL-induced) rat models [30]. EGFR inhibition also significantly reduced viability and ECM production in activated HSCs, inhibited their proliferation and α-SMA production, but did not affect parenchymal cells [31,32]. Moreover, inhibition of EGFR signaling by erlotinib and other specific inhibitors effectively prevented the progression of cirrhosis and regressed fibrosis in some animals (Table 1) [33,34].…”
Section: Egfrmentioning
confidence: 91%
“…11 Recently, we have shown that FGFR1 antagonism by either AZD4547 or siRNA silencing attenuates LPSinduced activation of hepatic stellate cells via suppressing inflammation. 12 These findings suggest that FGFR1 blockage may have the potential to reduce the severity of inflammatory injury in the kidney.…”
Section: Introductionmentioning
confidence: 94%
“…These data show that AZD4547 blocks TRAF6-related polyUb and possibly inhibits TAK1/NF-κB through this mechanism. Based on our previous research, 12 we tested whether LPS could induce the formation of the FGFR1/TRAF6 complex in NRK-52E cells. As shown in Figure 6B, co-immunoprecipitation showed that LPS challenge of NRK-52E cells for 15 to 30 min markedly increased the recruitment of TRAF6 to FGFR1, while the FGFR1 blocker AZD4547 completely prevented the FGFR1/TRAF6 interaction in NRK-52E cells ( Figure 6C).…”
Section: Azd4547 Modulates Traf6-related Polyubiquitination By Blockimentioning
confidence: 99%